Elemental Inventory in Fish Otoliths Reflects Natal Origin of Atlantic Herring (Clupea harengus) From Baltic Sea Juvenile Areas - Moll, Dorothee; Kotterba, Paul; Jochum, Klaus Peter; von Nordheim, Lena; Polte, Patrick (Frontiers in Marine Science, 2019)
Despite centuries of human exploitation and research on Atlantic herring (Clupea harengus) in Europe, there is still much uncertainty on where major nursery areas are located. However, understanding the quantitative contribution of particular coastal systems to adult fish populations is of utmost importance to secure sustainable fish resources. Routinely, marker elements indicating certain hydrological conditions, which are incorporated into calcified structures, the so-called otoliths, are used to trace the origin of fish. However, as in the Baltic Sea, small and large scale salinity gradients potentially masking specific salinity signals. Based on the entire inventory of otolith core elements, also including heavy metals, we developed a unique elemental fingerprinting index (EFI), allowing comparisons of multi-elemental chemical signatures from within and between herring juvenile areas. Our results show significantly distinct chemical “fingerprints” on the scale of particular bays and estuaries, which were not detectable with the usual marker elements. We further demonstrate that heavy metals levels drive the potential to distinguish natal origin of herring. These findings provide an essential baseline for further studies on the impact of small scale productivity for exploited fish resources and central components of marine food webs.